2011
DOI: 10.1111/j.1745-4565.2011.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Excision, Swabbing and Rinsing Sampling Methods to Determine the Microbiological Quality of Broiler Carcasses

Abstract: Skin excision, swabbing with cotton wool and whole carcass rinse are three common sampling methods of poultry carcasses.The objective of this study was to compare the three different sampling methods for enumeration and monitoring of bacteria on broiler carcasses. Total viable counts, Pseudomonas spp., lactic acid bacteria, Brochothrix thermosphacta and Enterobacteriaceae recovered by each sampling method were enumerated using the pour plate technique. Rinsing and excision recovered a similar level (P > 0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…As regards sampling method it has been demonstrated that, although tissue excision (both skin and meat) provided the highest counts of indicator microorganisms, the rinsing method is fully comparable with tissue excision, when used for process hygiene assessment purpose (Cox et al, 2010;Gill, Badoni, Moza, Barbut, & Griffiths, 2005), while the swabbing method is less effective (Cossi, de Almeida, Dias, de Arruda Pinto, & Nero, 2012;Zhang, Ye, Xu, Zhou, & Cao, 2012). However, when bacteria such as E. coli are present at low levels on poultry carcass portions, rinsing is the most effective technique compared with excision sampling and swabbing represents a valid alternative.…”
Section: Risk Of Bias Across Studiesmentioning
confidence: 95%
“…As regards sampling method it has been demonstrated that, although tissue excision (both skin and meat) provided the highest counts of indicator microorganisms, the rinsing method is fully comparable with tissue excision, when used for process hygiene assessment purpose (Cox et al, 2010;Gill, Badoni, Moza, Barbut, & Griffiths, 2005), while the swabbing method is less effective (Cossi, de Almeida, Dias, de Arruda Pinto, & Nero, 2012;Zhang, Ye, Xu, Zhou, & Cao, 2012). However, when bacteria such as E. coli are present at low levels on poultry carcass portions, rinsing is the most effective technique compared with excision sampling and swabbing represents a valid alternative.…”
Section: Risk Of Bias Across Studiesmentioning
confidence: 95%
“…Swabbing and excision offer practical advantages over carcass rinse, because of the ease and rapidity of sample collection and the smaller amount of enrichment medium required (Zhang et al, 2011). Swabbing and excision offer practical advantages over carcass rinse, because of the ease and rapidity of sample collection and the smaller amount of enrichment medium required (Zhang et al, 2011).…”
mentioning
confidence: 99%
“…As far as swabbing is concerned, it is generally accepted that for poultry carcasses, this method is less effective in recovering indicator bacteria than excision or rinsing Zhang et al, 2011;Cossi et al, 2012). The lower recovery level obtained by using swabbing method could be due to the topography of the poultry skin or to the attachment of bacteria to the skin (Zhang et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The International Organization for Standardization (ISO) has given recommended sampling methods for different types of food (e.g., ISO/TS 17728:2015 for food and animal feed, ISO 707:2008 for milk and milk products, and ISO 17604:2015 for carcasses). For example, excision, swabbing, and rinsing are three common methods for poultry carcasses sampling (Zhang, Ye, Xu, Zhou, & Cao, 2012). Generally, they are applicable with acceptable bacteria recoveries.…”
Section: Challenges In the Development Of Salmonella Biosensorsmentioning
confidence: 99%